KINERJA KEUANGAN SEBELUM DAN SESUDAH PANDEMI COVID-19 - Pesak, Pricilia Joice; Banea, Agnes Eyne; Gazali, Ahmad (Kurs : Jurnal Akuntansi, Kewirausahaan dan Bisnis, 2023)
This research aims to determine and analyze differences in financial performance between during and after COVID-19 in primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI). Financial report analysis uses profitability, liquidity, solvency, and activity ratios, from each ratio one ratio is taken to analyze, namely, net profit margin, current ratio, debt to asset ratio, and total asset turnover ratio. With a population of 117 companies in Indonesia's primary consumer goods sector, the research sample was selected using a purposive sampling method and found as many as 91 companies in the primary consumer goods sector on the Indonesia Stock Exchange (BEI) for the period 2020 - 2021. The type of data used in the research is quantitative data obtained from the financial reports of companies in the primary consumer goods sector on the Indonesia Stock Exchange. The analytical method used is the Wilcoxon signed-rank test. The research results show a difference in financial performance during and after Covid-19 as measured by the net profit margin and total asset turnover ratio, there is no difference in financial performance during and after Covid-19 as measured by the current ratio and debt to asset ratio Penelitian ini bertujuan untuk mengetahui dan menganalisis perbedaan kinerja keuangan antara saat dan setelah covid-19 pada perusahaan sektor barang konsumen primer yang terdaftar di Bursa Efek Indonesia (BEI). Analisis laporan keuangan menggunakan rasio profabilitas, likuiditas, solvabilitas dan aktivitas yang dari masing-masing rasio diambil satu rasio untuk menganalisis yaitu, net profit margin, current ratio, debt to asset ratio dan total asset turnover ratio. Dengan populasi 117 perusahaaan sektor barang konsumen primer di Indonesia, sampel penelitian dipilih dengan menggunakan metode purposive sampling dan didapati sebanyak 91 perusahaan sektor barang konsumen primer di Bursa Efek Indonesia (BEI) periode 2020 – 2021. Jenis data yang digunakan dalam penelitian adalah data kuantitatif yang diperoleh dari laporan keuangan perusahaan sektor barang konsumen primer di Bursa Efek Indonesia. Metode analisis yang digunakan adalah Uji Beda Wilcoxon signed rank test. Hasil penelian menunjukan bahwa terdapat perbedaan kinerja keuangan saat dan sesudah Covid-19 yang diukur dengan net profit margin dan total asset turnover ratio, tidak terdapat perbedaan kinerja keuangan saat dan sesudah covid-19 yang diukur dengan current ratio dan debt to asset ratio.